2018
DOI: 10.3389/fnmol.2017.00429
|View full text |Cite
|
Sign up to set email alerts
|

Intracerebroventricular Administration of 192IgG-Saporin Alters Expression of Microglia-Associated Genes in the Dorsal But Not Ventral Hippocampus

Abstract: One of important aspects of development of Alzheimer’s disease is degeneration of septal cholinergic neurons that innervate the hippocampus. We took advantage of widely used model of cholinergic deficit in the hippocampus, intracerebroventricular administration of 192IgG-saporin (Ig-saporin), to analyze the postponed consequences of cholinergic deficit in different parts of the hippocampus. We studied effects of the immunotoxin on the behavior of rats and gene expression in the dorsal and ventral hippocampus u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 39 publications
3
30
2
Order By: Relevance
“…DH appears to be primarily responsible for the cognitive functions of the hippocampus (Moser & Moser, 1998;Sahay & Hen, 2007;Barkus et al, 2010;Fanselow & Dong, 2010), which is consistent with our finding that that genes associated with learning and memory were only impacted in DH. Our findings also add to evidence suggesting that DH is more vulnerable to neuroinflammation and other pathology than VH (Fuster-Matanzo et al, 2011;Stouffer et al, 2015;Dobryakova et al, 2017;Dobryakova et al, 2019;Tournier et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…DH appears to be primarily responsible for the cognitive functions of the hippocampus (Moser & Moser, 1998;Sahay & Hen, 2007;Barkus et al, 2010;Fanselow & Dong, 2010), which is consistent with our finding that that genes associated with learning and memory were only impacted in DH. Our findings also add to evidence suggesting that DH is more vulnerable to neuroinflammation and other pathology than VH (Fuster-Matanzo et al, 2011;Stouffer et al, 2015;Dobryakova et al, 2017;Dobryakova et al, 2019;Tournier et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Importantly, the PVN is a critical component of the neural circuitry that underlies thirst (Cohn et al, 1984;Krishnan & Nestler, 2011;Dardiotis et al, 2012;Dobryakova et al, 2017) and our PCR gene array findings indicate that HF induces a massive decrease in gene expression in PVN.…”
Section: Discussionmentioning
confidence: 62%
“…It was found that lesion of BFCN was not associated with changes in mRNA level of the mentioned channels in the frontal cortex [125]. Similarly, MS/DBB and MS/NBM lesions also did not alter mRNA expression of majority of mentioned channels in the hippocampus [126,127]. Presumably, loss of cholinergic afferentation altered translation of some mRNAs but this hypothesis requires further examination.…”
Section: Alzheimer's Diseasementioning
confidence: 93%
“…Recently, we have applied a transcriptomic approach to study whether 192IgG-saporin induces neuroinflammatory consequences in the hippocampus. Administration of immunotoxin into the cerebral ventricles resulted in moderate impairments of cognitive functions which were associated not only with loss of cholinergic neurons in the medial septum, but also with loss of neurons in the CA3 field of the hippocampus [124,126]. Microglia proliferation was observed in the dorsal hippocampus and in the white matter.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation